Fibrous dysplasia coexisting with aneurysmal bone cyst in the skull base: A case report - Andrés Felipe Herrera Ortiz; Nury Tatiana Rincón Cuenca; Valeria del Castillo Herazo; Diana Marcela Oliveros Jiménez; Laura García Maestre; Mary Eugenia Posada; Luz Angela Moreno (Radiology Case Reports)
The coexistence of fibrous dysplasia and aneurysmal bone cyst in the craniofacial region is extremely rare. This article presents a unique case involving the skull base, diagnosed using computed tomography and magnetic resonance. Imaging revealed a characteristic expansile mass with a ground-glass appearance alongside cystic areas exhibiting fluid-fluid levels, indicative of fibrous dysplasia and aneurysmal bone cyst. Surgical resection was performed successfully, although significant intraoperative hemorrhage was encountered, leading to hypovolemic shock and cardiorespiratory arrest. This case underscores the essential role of imaging in accurate diagnosis and highlights the bleeding risks associated with surgical treatment of fibrous dysplasia with aneurysmal bone cyst. Preoperative embolization is suggested as a strategy to mitigate bleeding risk during surgery.